Soil Heavy Metals Soil Heavy Metals - Sherameti, Irena; Varma, Ajit.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Human activities have dramatically changed the composition and organisation of soils. Industrial and urban wastes, agricultural application and also mining activities resulted in an increased concentration of heavy metals in soils. How plants and soil microorganisms cope with this situation and the sophisticated techniques developed for survival in contaminated soils is discussed in this volume. The topics presented include: the general role of heavy metals in biological soil systems; the relation of inorganic and organic pollutions; heavy metal, salt tolerance and combined effects with salinity; effects on abuscular mycorrhizal and on saprophytic soil fungi; heavy metal resistance by streptomycetes; trace element determination of environmental samples; the use of microbiological communities as indicators; phytostabilization of lead polluted sites by native plants; effects of soil earthworms on removal of heavy metals and the remediation of heavy metal contaminated tropical land.
Soil: The Living Matrix -- Definition of (3z(BHeavy Metals(3y (Band Their Role in Biological Systems -- Soil Microbial Diversity in Relation to Heavy Metals -- Uptake and Effect of Heavy Metals on the Plant Detoxification Cascade in the Presence and Absence of Organic Pollutants -- Arbuscular Mycorrhiza, Heavy Metal,and Salt Tolerance -- Quantitative Analyses of Trace Elements in Environmental Samples: Options and (Im)possibilities -- At the Crossroads of Metal Hyperaccumulation and Glucosinolates: Is There Anything Out There? -- Plants Under Heavy Metal Stress in Saline Environments -- Utilizing Microbial Community Structure and Function to Evaluate the Health of Heavy Metal Polluted Soils -- Streptomycete Heavy Metal Resistance: Extracellular and Intracellular Mechanisms -- Effects of Heavy Metals on Soil Enzyme Activities -- Effect of Heavy Metals on Saprotrophic Soil Fungi -- Copper-Containing Oxidases: Occurrence in Soil Microorganisms, Properties, and Applications -- Biomethylation of Heavy Metals in Soil and Terrestrial Invertebrates -- Phytostabilization of Lead-Polluted Sites by Native Plants -- Impact of Heavy Metals on Sugarcane -- Effects of Earthworms on the Availability and Removal of Heavy Metals in Soil -- Phytoremediation of Heavy Metal Contaminated Soils -- Remediation of Heavy Metal Contaminated Tropical Land.s
Keywords: Life sciences; Agriculture; Biochemistry; Soil conservation; Environmental pollution; Life Sciences; Agriculture; Soil Science & Conservation; Plant Biochemistry; Terrestrial Pollution